Nursing and informatics for the 21st century : embracing a digital world. Book 1 Realizing digital health, bold challenges, and opportunities for nursing - Delaney, Connie White; Weaver, Charlotte A.; Sensmeier, Joyce; Pruinelli, Lisiane; Weber, Patrick, 1966- ([Place of publication not identified] : Productivity Press, 2022)
In just the past decade, the emergence of digital health has finally become palpable. Enhanced by the pandemic, social justice events, and planetary health urgency, Realizing Digital Health - Bold Challenges and Opportunities for Nursing explores that evolution with a focus on capturing the current state of digital health. Anchored in an introduction to digital health, new technologies, opportunities, and challenges are described. Consideration of the opportunities and challenges of digital health calls for specific attention to ethical considerations. This book includes a current state synopsis of healthcare in the USA, with the inclusion of specific implications for nursing leaders and executives. Engagement of the people (patients, families, communities) working in partnership to enhance health is described. Information management and the necessary definition and access to data are discussed with a particular explication of the function of information management and operational decision-making. The challenges and learnings related to informatics drawn from the experiences of leaders in large health systems shed insight into the current state of informatics-enabled digital health and healthcare. The global example of the integration of technology, nursing, and health systems expands our knowledge of the current state as well as explores possibilities. This book concludes with a commitment to and description of the current state of teamwork and the integral role/functions within informatics, nursing, and healthcare. This book provides the reader with a succinct overview of digital technologies, a reality-anchored description of the current state in the USA and globally and highlights the core foundation and integration of informatics and information management. This book stimulates thought and actions to advance digital health within a full partnership among the people, organizations, systems, and global imperatives including planetary survival. This book lifts up the next era calling for full teamwork, collaboration, and partnership as we emerge into a true global community. Nursing and Informatics for the 21st Century - Embracing a Digital World, 3rd Edition is comprised of four books which can be purchased individually: Book 1: Realizing Digital Health - Bold Challenges and Opportunities for Nursing Book 2: Nursing Education and Digital Health Strategies Book 3: Innovation, Technology, and Applied Informatics for Nurses Book 4: Nursing in an Integrated Digital World that Supports People, Systems, and the Planet.
Chapter 1: Digital Health Ecosystems: A Strategy for Transformation of Health Systems in the Post Pandemic Future Anne W. Snowdon, PhD, RN, FAAN, Professor, Strategy and Entrepreneurship, Odette School of Business, University of WindsorChapter 2: Digital Health and New Technologies Whende M. Carroll, MSN, RN-BC, FHIMSS, Director, Clinical Optimization, Contigo HealthChapter 3: Opportunities and Challenges for Digital Health AdvancementGillian Strudwick, PhD, RN, FAMIA, Chief Clinical Informatics Officer and Scientist, Centre for Addiction and Mental Health; Assistant Professor, Institute of Health Policy, Management and Evaluation, University of TorontoSanaz Riahi, PhD, RN, Vice President, Practice, Academics & Chief Nursing Executive, Ontario Shores Centre for Mental Health Sciences; Lecturer, Department of Psychiatry, University of TorontoNicholas R. Hardiker, PhD, RN, FACMI, FAAN, Professor of Nursing & Health Informatics, University of Huddersfield, UKChapter 4: Ethical Considerations in Digital HealthPirkko Kouri, PhD, PHN, RN, Finnish Society of Telemedicine and eHealth/International Society for Telemedicine & eHealthMinna Kaija-Kortelainen, MSSc, Bachelor of Law, Registered Social Worker, Senior Lecturer, Savonia University of Applied SciencesMargaret Ann Kennedy, PhD, RN, Senior Principal, Accenture, CanadaRiitta Turjamaa, PhD, PHN, RN, Manager, Savonia University of Applied Sciences and post doc researcher, Department of Nursing Science, University of Eastern FinlandChapter 5: U.S. Health and Healthcare Current State -- Nurse Executives Robyn Begley, DNP, RN, NEA-BC, FAAN, AONL Chief Executive Officer, AHA Senior Vice President and Chief Nursing Officer, American Organization for Nursing Leadership (AONL)Laura Reed, DNP, MBA, RN, Executive Vice President, Chief Nursing Executive, and Chief Operating Officer, M Health FairviewJulibeth Lauren, PhD, APRN, ACNS-BC, Vice-President, Practice and Clinical Education, M Health FairviewChapter 6: Engage the People -- Health Informatics and Personal Health ManagementAnne Moen, PhD, RN, FACMI, FIAHSI, Professor, Institute for Health and Society, Faculty of Medicine, University of OsloAmy Cramer, BSN, MMCi, CPHQ, Director, Global Product Development Strategic Partnerships, Pfizer LimitedCatherine Chronaki, MSc, DiplEng, Secretary General, HL7 Europe FoundationChapter 7: Information Management in Nursing Leaders' Operational Decision-MakingLaura-Maria Peltonen, PhD, Docent, FEANS, Department of Nursing Science, University of TurkuChapter 8: Informatics in Large Health Systems: Organization, Transformation and Nursing Informatics Leadership Perspectives Sheila Ochylski, DNP, RN-BC, FAMIA, Chief Nurse Informatics Officer, U.S. Department of Veterans AffairsRebecca Freeman, PhD, RN, FAAN, FNAP, Vice President for Health Informatics, University of Vermont Health NetworkChapter 9: Nursing Informatics within Health Systems -- Global Comparison Fabio D'Agostino, PhD, RN, Associate Professor of Nursing, Saint Camillus International University of Health and Medical SciencesMiriam de Abreu Almeida, PhD, RN, Full Professor, School of Nursing, Universidade Federal do Rio Grande do SulFederalAline Tsuma Gaedke Nomura, PhD, RN, Radiology Service Charge Nurse, Hospital de Clínicas de Porto AlegreJude L. Tayaben, PhD, RN, Assistant Professor, College of Nursing, Benguet State UniversityChapter 10: South Africa's Healthcare Systems, Technology and Nursing Graham Wright, MPhil, MBA, DN (Lon), Cert Ed, FBCS, FIAHSI, SRN, RMN, RNT, Professor Extraordinarius, University of South Africa; Chair, SAHIA Working Group, HELINA Education Working GroupHelen J. Betts, EdD, MEd (SEN), BA, PGCEA, SRN, SCM, ADM, MTD, HELINA Education Working GroupChrispin Kabuya, MSc, BSc, Walter Sisulu UniversityHenry Adams, B.Comn, InterSystems Corporation, South AfricaChapter 11: Teamwork and Informatics: Capturing the Work of Nurses as Team MembersKristen K. Will, PhD, MHPE, PA-C, College of Health Solutions, Arizona State UniversityGerri Lamb, PhD, RN, FAAN, Edson College of Nursing and Health Innovation, Arizona State University
OCLC-licensed vendor bibliographic record.
Keywords: Nursing informatics; Nursing -- Data processing; Information storage and retrieval systems -- Nursing; MEDICAL / Administration; MEDICAL / Nursing / Management & Leadership; MEDICAL / Hospital Administration & Care